Longitudinal patient-reported outcomes 1 year after thoracoscopic segmentectomy versus lobectomy for early-stage lung cancer: a multicentre, prospective cohort study protocol. Issue 1 (19th January 2023) - Gao, Xin; Dai, Wei; Zhang, Qi; Liu, Wenwu; Liu, Yangjun; Yang, Lingjia; Wei, Xing; Shi, Qiuling; Pompili, Cecilia; Pu, Yang; Xie, Shaohua; Xiang, Run; et al.
Abstract : Introduction: Segmentectomy and lobectomy are the main surgical procedures for early-stage lung cancer. However, few studies have analysed patient-reported outcomes after segmentectomy versus lobectomy. This study aims to compare patient-reported outcomes—such as symptoms, daily functioning and quality of life—between thoracoscopic segmentectomy and lobectomy for early-stage lung cancer during the 1 year after surgery. Methods and analysis: Overall, 788 newly diagnosed patients with early-stage lung cancer (tumour size ≤2 cm), who are scheduled to undergo thoracoscopic segmentectomy or lobectomy, will be recruited in this multicentre, prospective cohort study. The patients will receive standardised care after surgery. The Perioperative Symptom Assessment for Lung Surgery—a validated lung cancer surgery-specific scale—will be used to assess the symptoms and functions at baseline, at discharge and monthly after discharge for 1 year. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 and Lung Cancer module 29 will be used to assess the patients' quality of life at the same time points. The primary outcome will be the shortness of breath scores during the first year after thoracoscopic segmentectomy and lobectomy and will be compared using mixed-effects models. The secondary outcomes will include other symptoms, indicators of daily functioning, quality of life scores and traditional clinical outcomes. These will be compared using mixed-effects models and the Student's t-test, non-parametric test or Χ 2 test. Propensity score matching will be used to ensure an even distribution of known confounders between the groups. Ethics and dissemination: The Ethics Committee for Medical Research and New Medical Technology of Sichuan Cancer Hospital approved this study (approval number: SCCHEC-02-2022-002). All participants will be instructed to provide informed consent. The manuscript is based on protocol version 3.0. The study results will be presented at medical conferences and published in peer-reviewed journals. Trial registration number: ChiCTR2200060753.